2010
DOI: 10.3324/haematol.2009.017665
|View full text |Cite
|
Sign up to set email alerts
|

Digenic mutations in severe congenital neutropenia

Abstract: Severe congenital neutropenia a clinically and genetically heterogeneous disorder. Mutations in different genes have been described as causative for severe neutropenia, e.g. ELANE, HAX1 and G6PC3. Although congenital neutropenia is considered to be a group of monogenic disorders, the phenotypic heterogeneity even within the yet defined genetic subtypes points to additional genetic and/or epigenetic influences on the disease phenotype. We describe congenital neutropenia patients with mutations in two candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
(34 reference statements)
3
38
1
1
Order By: Relevance
“…The dual contribution of the type I and type II IFNs to susceptibility to viral infection is illustrated by the IFNAR/IFNGR double-knockout mice, which are more susceptible The unbiased approach inherent in next-generation sequencing has shown that approximately 5% of sequenced patients have disease-causing multiloci variants (14). Multigenic mutations have been shown to shape the phenotype of patients with autoimmunity, severe congenital neutropenia, and familial HLH (15)(16)(17). This is the first report, to our knowledge, of a digenic human primary immunodeficiency caused by defects specific to IFNAR1 and IFN-GR2.…”
Section: C266fsmentioning
confidence: 99%
“…The dual contribution of the type I and type II IFNs to susceptibility to viral infection is illustrated by the IFNAR/IFNGR double-knockout mice, which are more susceptible The unbiased approach inherent in next-generation sequencing has shown that approximately 5% of sequenced patients have disease-causing multiloci variants (14). Multigenic mutations have been shown to shape the phenotype of patients with autoimmunity, severe congenital neutropenia, and familial HLH (15)(16)(17). This is the first report, to our knowledge, of a digenic human primary immunodeficiency caused by defects specific to IFNAR1 and IFN-GR2.…”
Section: C266fsmentioning
confidence: 99%
“…Activating mutations in the WAS gene have been found to be responsible for some cases of X-linked-SNC [54,55] (EO, IV, V, 8.1, B). Finally as patients with digenic mutations have been found [56], mutation search in a second gene known to be involved in SCN should also be considered. In case these investigations fail to detect a genetic cause of SCN, the panel recommended to carefully re-evaluate history, clinical symptoms and specific laboratory tests.…”
Section: (Eo 9 A)mentioning
confidence: 99%
“…This could explain the unexpected occurrence of di-genic mutations (ELANE and HAX1) in a single SCN patient and the presence of an ELANE mutation in a patient from one of the Kostmann families, who had unaffected HAX1 genes. 11,13 These phenomena are unlikely to happen by chance, given the rarity of ELANE and HAX1 mutations in the healthy population. Similarly, host factors may have influenced the course of the disease in the two patients reported by Rolf Kostmann, who had significantly milder symptoms than others within the same pedigree.…”
Section: Scn With Mutations In Hax1 (Hax1-scn)mentioning
confidence: 99%